Authentic Assessment Objective Working Standardmanaegementstrategy Training for Supervisor with Law and Computerized Value - Pamuji, Wirawan; Gde Brahupadhya Subiksa; Eko Budiyanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Standard Official of working performance requires authentic operational procedure to enhance staffs character of working regarding quality of Human Resource Development. It is required real application of Authentic Supervising system at Company. The Research applies Development Method to improve adequate assessment during working with staff partners at work supervised with law, management and computerized standard training for adequate Quality in working due that the training. The application of this design is to analyze the adherent influence between real process score of the working field and further working quality overview as planned design